Bedrijfswagens: diagnostiek en uitdagingen van een fiscaal regime - Xavier May; Thomas Ermans; Nils Hooftman (Brussels Studies)
There were approximately 650 000 company cars in Belgium in 2016 of a total of 5 700 000 cars on the roads. It may be estimated that approximately 100 000 company cars enter, exit or are driven in the Brussels Region every day: they therefore undoubtedly have a significant impact on regional mobility. This article first attempts to describe the tax system for company cars along with the specificities of the cars concerned. Next, this synopsis describes the characteristics of the companies which provide these cars and the profile of the employees who use them. An analysis of the distances travelled by company cars and their impact on road traffic is conducted, as well as an assessment of the impact of the system on taxes and salaries. Finally, a brief analysis of the environmental impact of company cars is carried out concerning the production of greenhouse gases as well as the impact of emissions on human health. The challenges and debates related to company cars in Brussels and in Belgium are put into perspective at the end of the article.